(untitled) (Journal of Educational Sciences, 2021)
High-quality education is the key to a successful future. Currently, the importance of the use of digi- tal technologies in improving the quality of education is very high. Its application and the output of its results directly depend on the professional knowledge, skills and abilities of each teacher. The purpose of the research work: to theoretically justify the formation of teachers’ qualifications for the use of digital educational technologies and to test its effectiveness. Scientific novelty and theoretical significance of the research: the meaning and content of the con- cepts of “Digital Education”, “Digital educational Technologies” were clarified; each teacher was pro- vided with information about the auxiliary services Videoscribe, Padlet, Pixton, Flippity, Socrative, Hot potatoes, No Hands, Quizizz, ClassDojo, Learnis, Tilda Publishing for a productive, understandable and interesting lesson; an additional auxiliary website was created. In accordance with the incredible pace of development of new technologies, this site will be updated and updated with new information over time. A survey of 50 teachers was conducted on the use of digital resources. It was found that the services most widely used by teachers are: Kahoot – 82.5%; Prezi – 66.7%; Quizlet – 65%; Bandicam – 65%; Learning Apps – 64.1%. Digitalization is changing the social paradigm of human life, which opens up opportunities for new knowledge and expanding a person’s worldview. Digital technologies are becoming not only a tool, but also a new environment for human existence, life and professional activity. Key words: digitalization, digital educational technologies.